Science and providence: God's interaction with the world - Polkinghorne, John C. (Templeton Foundation Press, 2005)
Introduction xx -- The problem xx -- Embodiment and action xx -- Providence xx -- Miracle xx -- Evil xx -- Prayer xx -- Time xx -- Incarnation and sacrament xx -- Hope.